2012
DOI: 10.1093/eurheartj/ehs121
|View full text |Cite
|
Sign up to set email alerts
|

Threshold crossing of device-based intrathoracic impedance trends identifies relatively increased mortality risk

Abstract: AimsThreshold crossings of impedance trends detected by implanted devices have been associated with clinically relevant heart failure events, but long-term prognosis of such events has not been demonstrated. The aim of this study is to examine the relationship between alterations in intrathoracic impedance and mortality risk in patients with implantable devices.Methods and resultsWe reviewed remote monitoring data in the de-identified Medtronic CareLink® Discovery Link that captured intrathoracic impedance tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…Previous studies demonstrated that the presence of an OptiVol fluid index crossing was associated with increased mortality (2). In fact, patients with one or more crossings during the first six months after implant were shown to be at 2.15 times higher risk of a mortal event than patients with no OptiVol crossings.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies demonstrated that the presence of an OptiVol fluid index crossing was associated with increased mortality (2). In fact, patients with one or more crossings during the first six months after implant were shown to be at 2.15 times higher risk of a mortal event than patients with no OptiVol crossings.…”
Section: Discussionmentioning
confidence: 98%
“…In these previous studies, an impedance-derived fluid index (hereafter called “OptiVol fluid index”) was obtained using a cumulative sum mathematical model that calculates the differences between impedance measured in ohms (hereafter called directly “measured impedance”) and a reference impedance; the OptiVol fluid index was expressed in ohm-days. It was demonstrated that when the OptiVol fluid index value exceeded 60 ohm-days, the crossing of this threshold value predicted both increased morbidity and mortality (27). This calculated OptiVol fluid index was chosen instead of the directly measured impedance because of several anticipated confounding limitations of the direct impedance measurement.…”
mentioning
confidence: 99%
“…A fluid index value at or above the threshold (i.e., “fluid index threshold crossing” [FIC]) may be an indicator of thoracic fluid accumulation. Although individual threshold FIC events are not always associated with HF symptoms, FIC events have been shown to be strongly associated with increased risk of HF hospitalization and all‐cause mortality …”
Section: Methodsmentioning
confidence: 99%
“…3 Hence, recognizing alterations in impedance trends may uncover vulnerabilities that can be associated with adverse clinical events. [4][5][6][7] Meanwhile, accessing the information requires no special equipment or complex logistics, and there is no additional cost. In fact, the data are already incorporated into routine remote and in-person cardiac implantable electronic device checks.…”
Section: See Article By Zile Et Almentioning
confidence: 99%
“…Changes between the baseline and the subsequent measurements at 9 to 12 months post implant added predictive value. 9 In contrast to previous study, which have examined the calculated impedance trends and mortality relationship, 6 impedance measurements from the first 6 months after implant were censored in this study to allow time for the signal to stabilize and no algorithmic manipulation of the data was performed. Various measurement intervals were examined.…”
Section: Small and Tangmentioning
confidence: 99%